RAG-dependent peripheral T cell receptor diversification in CD8(+) T lymphocytes - Serra, Pau (National Academy of Sciences, 2002)
Rearrangement of T cell receptor (TCR) genes is driven by transient expression of V(D)J recombination-activating genes (RAGs) during lymphocyte development. Immunological dogma holds that T cells irreversibly terminate RAG expression before exiting the thymus, and that all of the progeny arising from mature T cells express the parental TCRs. When single pancreatic islet-derived, NRP-A7 peptide-reactive CD8(+) T cells from nonobese diabetic (NOD) mice were repeatedly stimulated with peptide-pulsed dendritic cells, daughter T cells reexpressed RAGs, lost their ability to bind to NRP-A7/K(d) tetramers, ceased to transcribe tetramer-specific TCR genes, and, instead, expressed a vast array of other TCR rearrangements. Pancreatic lymph node (PLN) CD8(+) T cells from animals expressing a transgenic NRP-A7-reactive TCR transcribed and translated RAGs in vivo and displayed endogenous TCRs on their surface. RAG reexpression also occurred in the PLN CD8(+) T cells of wild-type NOD mice and could be induced in the peripheral CD8(+) T cells of nondiabetes-prone TCR-transgenic B10.H2(g7) mice by stimulation with peptide-pulsed dendritic cells. In contrast, reexpression of RAGs could not be induced in the CD8(+) T cells of B6 mice expressing an ovalbumin-specific, K(b)-restricted TCR, or in the CD8(+) T cells of NOD mice expressing a lymphocytic choriomeningitis virus-specific, D(b)-restricted TCR. Extra-thymic reexpression of the V(D)J recombination machinery in certain CD8(+) T cell subpopulations, therefore, enables further diversification of the peripheral T cell repertoire.